(3CeKGd ef CbhGd GdCeGe Ydi Hf CHj WGdH cQe Gddg hLggs - (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3gPG eG Jcde Hg CejQ GdeDefjf Ydi Hf CHj WGdH bGd Ydgj GdSdGe GdUOb CeGfI hGdcPH NjGfI hGdEfUGa QGMI s
(3BNQgG (B:s
(3hbGd QH eaJhf HMSf Gdbhd ajg hbGd GdGSJaJGA Yf GdZOQ CYR ef GdKOb ajg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdNGeS YTQs
(3GfXQ GdeNWhW Qbe (B292s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs